KEMAMPUAN RESILIENSI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA: SYSTEMATIC LITERATUR REVIEW - Maarif, Samsul; AL-Ashri, Lazuardi Sastra; Khairunnisa, Rika (TRANSFORMASI, 2023)
Mathematical resilience is the most important part of mathematics so that students have the confidence to work on the mathematical problems they face. With this, students will be able to reflect and discuss the results of their mathematics learning so that they achieve success. This research was conducted using a systematic literature review method with the aim of determining trends and author distribution that link mathematical resilience with creative thinking. Research is limited to the last ten and was carried out with the help of Publish Or Perish (PoP) which is sourced from Google Scholar. The search show that there are 500 article metadata which are then stored in CSV type which are analyzed using Microsoft Excel. Next, the data is saved again in RIS form and analyzed with the help of VOS Viewer to see current research trends. The research results show that: 1) the trend of research development related to mathematical resilience over the last 10 years regarding mathematical resilience is still rarely linked to STEM, technology and science topics; 2) the distribution of resilience research is still dominated by middle school, high school, and collage students; 3) the research methods used are still mostly case studies, surveys and systematic literature reviews; 4) the largest sample in resilience research is 631 collage student, 384 high school students, and 99 teacher in survey research.